PENGEMBANGAN PERANGKAT PEMBELAJARAN BERDASARKAN MASALAH BERBASIS EDUTAINMENT UNTUK MELATIHKAN KREATIVITAS SISWA SMK JURUSAN OTOMOTIF PADA MATERI FLUIDA STATIS - Wasis Wasis; Muslimin Ibrahim (Universitas Negeri Surabaya, 2017)
The purpose of this research is to produce a Physics learning materials using Problem Based Instruction (PBI) model, which is valid, practical, and effective to Train creativity of student. This research is conducted through three phases from 4-D model, those are define, design, and develop. That instrument is tried out in XI grade Vocation High School of Senopati Sedati Sidoarjo academic year 2016/2017 with one group pretest-post test design. The learning instruments developed include: (a) syllabus, (b) Lesson Plan, (c) handout, (d) Work Sheet, (e) Assessment Sheet of creativity. Research variabels which can be measured are validity, practicality, and effectiveness of learning instrument. Data are collected using validity method, observation, test, questionnaires. Data are analyzed quantitatively descriptive and qualitatively. Research data shows that (a) developed learning instrument is categorized valid, (b) Learning process was going well, (c) training of student creativity produces increase on middle category, and (d) student gives positive feedback to learning had done. Based on analysis and discussion, concluded that Physics learning instrument using model of PBI based on education developed is valid, practical, and effective to train creativity of student